Effect of Calcination Conditions on Phase Formation and Characterization of BiFeO3-BaTiO3 powders synthesized by a solid-state reaction - S. Chandarak (2018)
A perovskite-type phase of solid solution of BiFeO3-BaTiO 3 powders were synthesized by a solid-state reaction via a rapid vibro-milling technique. The effect of calcination condition on the phase formation, and characterization of BiFeO3-BaTiO3 powders were investigated. The formation of the BiFeO3-BaTiO3 phase investigated as a function of calcination conditions by TG-DTA and XRD. Morphology, particle size and chemical composition have been determined via a combination of SEM and EDX techniques and vibrating sample magnetometer (VSM) was used to characterize the structures and magnetic properties of prepared samples. The rapid vibro-milling is employed for the first time in this work as a significant time-saving method to obtain single-phase BiFeO 3-BaTiO3 powders. © 2008 Trans Tech Publications, Switzerland.